New perspectives for fascioliasis in Upper Egypt's new endemic region: Sociodemographic characteristics and phylogenetic analysis of Fasciola in humans, animals, and lymnaeid vectors. - Alzahraa Abdelraouf Ahmad; Haidi Karam-Allah Ramadan; Waleed Attia Hassan; Mohammed Ageeli Hakami; Enas Abdelhameed Mahmoud Huseein; Sara Abdel-Aal Mohamed; Adnan Ahmed Mohamed; Nahed Ahmed Elossily (Public Library of Science (PLoS), 2022)
Background Fascioliasis is a significant vector-borne disease that has emerged in numerous tropical and subtropical countries causing severe health problems. Egypt is one of the fascioliasis endemic regions; however, the current situation in Upper Egypt is understudied, with only sporadic human cases or outbreaks. This study aims to highlight the sociodemographic characteristics of human fascioliasis in a newly emerged endemic area in Upper Egypt, along with risk factors analysis and the molecular characteristics of the fasciolid population in humans, animals, and lymnaeid snails. Methodology/principal findings The study reported Fasciola infection in patients and their close relatives by analyzing the risk of human infection. Morphological and molecular characterization was performed on lymnaeid snails. Multigene sequencing was also used to characterize fasciolids from human cases, cattle, and pooled snail samples. The study identified asymptomatic Fasciola infection among family members and identified the presence of peridomestic animals as a significant risk factor for infection. This is the first genetic evidence that Radix auricularia exists as the snail intermediate host in Egypt. Conclusions/significance This study revealed that Assiut Governorate in Upper Egypt is a high-risk area for human fascioliasis that requires additional control measures. Fasciola hepatica was the main causative agent infecting humans and snail vectors in this newly emerged endemic area. In addition, this is the first report of R. auricularia as the snail intermediate host transmitting fascioliasis in Upper Egypt. Further research is required to clarify the widespread distribution of Fasciola in Egypt's various animal hosts. This provides insight into the mode of transmission, epidemiological criteria, and genetic diversity of fasciolid populations in Upper Egypt.\.